El servicio de seguridad y salud en el trabajo - Ugaz, Mauro (2012)
The service of safety and health at workThe article maintains that, mainly, from the approval of Law 29783, Law of Occupational Safety and Health at Work, it has been internalizing the importance of implementation of regulations and measures to reinforce or emphasize safety and health at work. However, it is emphasized that until the appearing of regulatory norm of law, enterprises as well as workers will have to safeguard for implementing a service that they consider –technically– suitable to their place of work without having a referent clear normative, since the Law doesn’t detail the implementation of a security service and health at work. In this regard, the technic document entitled «Protocols of Medical Occupational Exams and Guidelines of Obligatory Diagnostic Medical Exams by activity», contains a series of regulations that permit to integrate and implement a suitable service and appropriated of health surveillance of workers.